The Interpretations of Eternalism in Reality Club’s 2112 - Pasopati, Rommel Utungga; Sasmita, Dimas Rakhmat; Santoso, Liora Samantha Valent; Kurniawati, Wiwin Anggraeni; Kartiningsih, Rindrah (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2024)
This paper exposes the matter of eternalism in the song of 2112 by Reality Club. By accentuating the theory of eternalism by J. M. E. McTaggart, eternalism is underlined in how all existence in time is equally real. In analysis, the song of 2112 depicts a love story that goes on since the couples were teenagers. Things are getting more complicated since they could not be together but they still have feelings of comfort and togetherness as if they live in eternal times. The memories keep going on though the time moves forward. It proves that the block universe of past, present and future events are all on an equal footing. In conclusion, the song reflects the matter of eternalism in the points of memories, not as past understandings, but as an open future towards any determinism in showing that any event is always interpreted through any matter of time.